The Effect of Achievement Motivation and Teacher Participation in Course Teacher Consultations (MGMP) in Dumai, Riau Province - Frianita Riswandi Gaban; Sri Kartikowati; Elfis Suanto (Journal of Educational Sciences, 2021)
This research is motivated by the competence of the Mathematics teacher of Dumai Junior High School which is below the national average value. This study aims to analyze how much influence of achievement motivation, teacher participation, and teacher participation in MGMP together on teacher competence. To achieve this goal, this paper used a survey research type with a quantitative approach. The research population was all Mathematics teachers of Dumai for Middle School who had participated in the 2015 UKG, totaling 88 people. With the total sampling technique, the entire population was determined as a sample. The data analysis used is descriptive statistical analysis and inferential statistical analysis. The results showed that there was a positive and significant influence of achievement motivation on the competence of Mathematics teachers by 26.3%. There is a positive and significant effect of teacher participation in the MGMP on the competence of Junior High School Mathematics teacher by 22.5%. There is a jointly significant effect of 30.8% achievement motivation and teacher participation. The achievement motivation variable has a greater influence than the teacher participation variable. This means that the high and low competence of junior high school mathematics teachers in Dumai can be influenced by achievement motivation and teacher participation in MGMP.